Effect of Practical Demonstration Strategy on Skills of Forward Roll and Headstand in Artistic Gymnastics for Students - Ameen Atta Hassan (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The use of practical demonstration techniques in teaching certain feats, such headstands and front rolls, is crucial for raising students' ability levels. Additionally, it improves their involvement and comprehension of skills in a more profound and unique way. The purpose of the study was to determine how students' front roll and headstand skills in artistic gymnastics were affected by practical demonstration techniques. Because the experimental research approach is consistent with tackling the topic under investigation, the researcher employed it. He created two comparable groups: the experimental group and the control group. For the academic year 2024–2025, the research community represented second-year students at the University of Wasit's College of Physical Education and Sports Sciences. A total of 110 students were divided among five classes, each with twenty-two students: A, B, C, D, and E. A lottery was used to choose Class (A) as the experimental group and Class (C) as the control group. The researcher came to the conclusion that some rolling abilities were developed as a result of the practical demonstration technique. Second-year students do headstands and forward rolls.